The Association Between High Birth Weight and Long-Term Outcomes—Implications for Assisted Reproductive Technologies: A Systematic Review and Meta-Analysis - Magnusson, Åsa; Laivuori, Hannele; Loft, Anne; Oldereid, Nan B.; Pinborg, Anja; Petzold, Max; Romundstad, Liv Bente; Söderström-Anttila, Viveca; Bergh, Christina (Frontiers in Pediatrics, 2021)
Background: Studies have shown that the prevalence of children born with high birth weight or large for gestational age (LGA) is increasing. This is true for spontaneous pregnancies, however children born after frozen embryo transfer (FET) as part of assisted reproductive technology (ART) also have an elevated risk. In recent years the practice of FET has increased rapidly and while the perinatal and obstetric risks are well studied, less is known about the long-term health consequences. Objective: The aim of this systematic review was to describe the association between high birth weight and LGA on long-term child outcomes. Data sources: PubMed, Scopus and Web of Science were searched up to January 2021. Exposure included high birth weight and LGA. Long-term outcome variables included malignancies, psychiatric disorders, cardiovascular disease and diabetes. Study selection: Original studies published in English or Scandinavian languages were included. Studies with a control group were included while studies published as abstracts and case reports were excluded. Data extraction: The methodological quality, in terms of risk of bias, was assessed by pairs of reviewers. Robins-I (www.methods.cochrane.org) was used for risk of bias assessment in original articles. For systematic reviews AMSTAR (www.amstar.ca) was used. For certainty of evidence, we used the GRADE system. The systematic review followed PRISMA guidelines. When possible, meta-analyses were performed. Results: The search included 11 767 articles out of which 173 met the inclusion criteria and were included in the qualitative analysis, while 63 were included in quantitative synthesis (meta-analyses). High birth weight and/or LGA was associated with low to moderately elevated risks for certain malignancies in childhood, breast cancer, several psychiatric disorders, hypertension in childhood and type 1 and 2 diabetes. Conclusions: Although the increased risks for adverse outcome in offspring associated with high birth weight and LGA, represents serious health effects in childhood and in adulthood, the size of these effects seems moderate. The identified risk association should however be taken into account in decisions concerning fresh and frozen ART cycles and is of general importance in view of the increasing prevalence in high birth weight babies.